A Potential Pitfall in POCUS of the Gallbladder: Beware of the Duodenum - Fan Yang; Brian Kohen; Sowmya Sanapala; Michael Halperin (CINQUILL Medical Publishers Inc., 2022)
It is estimated that 20 million people in the United States have gallbladder disease. Of the patients who present to the Emergency Department (ED) with abdominal pain, 3-10% have acute cholecystitis [1]. Point-of-care ultrasound (POCUS) evaluation of the biliary system is a valuable tool to diagnose gallbladder disease and can greatly expedite the diagnostic evaluation of patients. One source of error in POCUS of the gallbladder is imaging nearby structures that can mimic the gallbladder, such as the duodenum.